Efficacy of colimox® (a new combination of amoxicillin and colistin) in the control of experimentally induced necrotic enteritis in broiler chickens - Elbadawy, Mohamed; Aboubakr, Mohamed (International Journal of Pharmacology and Toxicology, 2017)
The aim of the present study was to determine the efficacy of amoxicillin and colistin either alone or in combination (colimox®) for control of experimentally induced C. perfringens infections in broiler chickens. Three hundred birds were used and divided into five groups (A, B, C, D and E, each of 60 bird). At the 14th day of age, birds in all groups (except group A) were inoculated orally with 0.5 mL of C. perfringens broth culture (109 CFU/mL). Two days later, drugs were orally administered once daily for five consecutive days as follow; Group A and B were left untreated. Group C, D and E were treated with amoxicillin (20 mg/kg b.wt), colistin (100000 IU /kg b.wt), colimox® (amoxicillin plus colistin), respectively. The efficacy of used drugs were determined on the basis of clinical symptoms, mortality rate, body weight, total feed consumption, feed conversion rate and scores of intestinal lesions. The minimum inhibitory concentration (MIC) of amoxicillin against C. perfringens was done by micro-broth dilution method and was ≤ 2 µg/mL. Efficacy results indicated that all used medications were effective (but with different degrees) in control of C. perfringens induced necrotic enteritis as expressed by significant (p<0.05) reduction of clinical signs, mortalities and intestinal lesion scores as well as improving the performance parameters in broiler chickens, however colimox® was the superior. It could be concluded that combination of amoxicillin and colistin (colimox®) was of a considerable value in control of necrotic enteritis in broiler chickens than using them separately.